ECONOMIC BEHAVIOUR PATTERNS IN TERMS OF MIXED ECONOMY IN POST-REFORM PERIOD (BASED ON THE DON DOCUMENTS) - O.M. MOROZOVA (Advanced Engineering Research)
Family records of several Cossack families demonstrate that market economic thinking was typical for Cossacks even in the prereform period. Thinking, behavior, moral and ethical arrangement of life among Don landowners of all categories were not only close to the  traditional Russian serfdom type, but also show that they were well informed about market economy. The author tries to prove that their observance of old fashioned traditions in currency and production can be explained not by their devotion to the customs, but by the profit it could bring to Cossacks in particular situations.